The changes in CD4+CD25high T cells and TGFβ1 levels in different stages of adult-onset Type 1 diabetes: Stages in T1D: differences in CD25high T cells and TGFβ1 - Miličić, Tanja; Jotic, Aleksandra; Markovic, Ivanka; Popadic, Dusan; Lalic, Katarina; Uskokovic, Veljko; Lukic, Ljiljana; Macesic, Marija; Stanarcic, Jelena; Stoiljkovic, Milica; Milovancevic, Mina; Rafailovic, Djurdja; et al. (Journal of Medical Biochemistry, 2024)
Background. Previous studies suggested important role of impairments in T cells subsets in different stages during type 1 diabetes (T1D) development, while data regarding CD25high T cells and transforming growth factor β1-TGFβ1, both T regulatory associated, still remains controversial. We analysed the level of (a) CD25high T cells (b) TGFβ1 in 17 first-degree relatives of patients with T1D in stage 1 (FDRs1) (GADA+, IA-2+); 34 FDRs in stage 0 (FDRs0) (GADA-, IA-2-); 24 recent-onset T1D in insulin requiring state (IRS); 10 patients in clinical remission (CR); 18 healthy, unrelated controls (CTR). Methods. T cell subsets were characterized by two-color immunofluorescence staining and flow cytometry, TGFβ1 was determined by ELISA, GADA, and IA-2 by RIA. Results. The level of CD25high T cells in FDRs1 was lower than controls, FDRs0, IRS, and CR (p
Keywords: CD4 CD25high T cells, first-degree relatives of patients with type 1 diabetes, TGFβ, type 1 diabetes